Explosive Adductor Exercise Effects on Range of Motion and Muscular Strength Variables Among Runners - Kumar, K. Satheesh (Innovare Journal of Education, 2025)
The purpose of the study was to find out the explosive adductor exercise effects on a range of motion and speed endurance variables among runners. To achieve the purpose of the study, thirty college-level runners were selected randomly as subjects from M.D.T. Hindu College and St. Johns College of Physical Education, Tirunelveli District, Tamil Nadu, India, and their ages ranged from 17 to 25 years. The subjects were divided into two groups in equal numbers (N = 15). Group I underwent explosive adductor exercise group and Group II acted as the control group who did not attend any special training other than their daily college schedule curriculum. The duration of the training period was restricted to six weeks for 5 days per week. The pre and post-test data were collected before and after the training period. The dependent variables, range of motion and speed endurance, were tested by standardized test items, range of motion and speed endurance consumption tests, respectively. The collected data from the two groups prior to and after the experimental treatments on selected variables, range of motion and speed endurance were statistically analyzed by using the statistical technique of dependent test and analysis of covariance (ANCOVA). In all the cases, the level of confidence was fixed at 0.05 significant. The result of the study indicated that the experimental group had shown significant improvement in the sit and reach test and 300 mts dash variables among college-level runners due to the effects of explosive adductor exercise. However, the control group did not show any significant improvement in selected variables such as range of motion and speed endurance.